Legal Politics of Fulfilling Constitutional Rights to Education and Health for Baduy Women: Intersections of Customary Law, State Policy, and Islamic Values - Ade Fartini; Eka Julaiha; Nina Chairina; Ni'matul Huda (International Journal of Nusantara Islam, 2026)
The 1999–2002 amendments to the 1945 Constitution significantly strengthened human rights protections in Indonesia, specifically regarding education and health. Despite these guarantees, indigenous women in the Baduy community face systemic barriers to accessing these constitutional rights. This research employs a juridical-empirical method to examine the legal politics of rights fulfillment in Kanekes Village. The investigation identifies that internal obstacles, rooted in the strict adherence to “Pikukuh” customary taboos, and external factors contribute to the unequal distribution of services. Furthermore, this study explores the religious dimension of Baduy identity, known as “Slam Wiwitan,” and its intersection with Islamic values prevalent in the surrounding Banten region. The results suggest that a collaborative legal politics model that integrates the “Papagahan” peer-learning concept and culturally sensitive health facilities is essential. This study concludes that fulfilling state obligations requires a synergy between national legislation, customary living law, and the religious nuances of the community to ensure rights are realized without eroding cultural identity.